EKSIBISIONISME Exhibitionism and Voyeurism in Live-Streaming Applications as Affection Labor - Eko Nugroho; Dida Dirgahayu; Karman; Djoko Walujo (LPPM Stikosa - AWS, 2023)
Despite having a positive impact on society, internet connectivity and accessibility have ethical consequences and have a real impact on Indonesian law. The impact of exhibitionism and voyeurism that we refer to in this work is exhibitionism and voyeurism. This practice is mediated through several new media-based communications venues. This article aims to explain these phenomena of exhibitionism and voyeurism from the perspective of a psychoanalytic framework and outline how the reification of the user into labor logic, and explain how the psychoanalytic process of consumerism is linked to nudity in live broadcasts. We collect information by monitoring the use of Live streaming applications (Bigo, Gogo-live, Tik Tok), either directly or indirectly through the YouTube program. This study concluded that consumerism, or voyeurism, occurs in live-chat streaming programs. The logic of capitalism and capitalization in the Internet and networking sectors encourage exhibitionism and voyeurism by users of live-streaming applications (labor). By turning audiences or content into commodities, voyeurism creates various commodities. In addition, nudity is a kind of merchandise from hard work that ethically has an impact like pornography which is regulated in the Indonesian legal system. Keywords: Exhibitionism; Voyeurism; Streaming Applications; Affection Labor.